Analisa Pengaruh Food Quality, Service Person Customer Orientation, Dan Physical Environment, Terhadap Repurchase Intention, Melalui Customer Satisfaction - Steffi Weliani (Universitas Multimedia Nusantara, 2015)
The purpose of this study to determine whether the proposed Repurchase Intention of B'Steak Gading Serpong restaurant’s consumers is affected by the Food Quality, Service Person Customer Orientation and Physical Environment through Customer Satisfaction. B'Steak Gading Serpong is a western style restaurant with an interesting concept of fine dining which is the object of this study. The theoretical model in this study presented with 4 hypotheses to be tested using Structural Equation Model, with sample of 110 respondents aged 17 years or older who had once come to visit B'Steak Gading Serpong. Results from the data analysis showed that the Food Quality, Service Person Customer Orientation and Physical Environment through Customer Satisfaction have positive influence on Repurchase Intention in B'Steak Gading Serpong restaurant. Keywords: Reward, Extrinsic Reward, Intrinsic Reward, Employee Performance